Flaxseed oil ameliorates mercuric chloride-induced liver damage in rats - AlRamadneh, Tareq Nayef; AlQurashi, Naif; Khan, Mohd Sajjad Ahmad; Hashimi, Saeed Mujahid; Javaraiah, Rajesh; Al-Ostoot, Fares Hezam; Abu Alhaija, Abed Alkarem (Elsevier Gmbh, 2022)
Background: Mercury is a relentless pollutant, and its toxicity contributes to significant health problems due to exposure to the environment. The present study has determined the impact of flaxseed oil on mercuric chloride (HgCl2)-mediated hepatic oxidative toxicity in rats. Methods: Twenty-four healthy male Wistar rats were divided into four groups with six animals in each group. Group-A was the Control group treated with saline; Group-B received 1.0 ml oral dosage of flaxseed oil; Group-C was given 200 mu l intraperitoneal injection of HgCl2, and Group-D received 1.0 ml oral dosage of flaxseed oil (one hour after treatment with 200 mu l intraperitoneal injection of HgCl2. Results: Mercuric chloride (HgCl2) increased the production of malondialdehyde (MDA), reactive oxygen species (ROS), glutathione (GSH), and the concentration of HgCl2 in the liver tissue with a simultaneous decrease in the activities of Superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). Furthermore, serum HgCl2 elevated the activity of alanine transaminase (ALT) and Lactate dehydrogenase (LDH). Histopathological changes showed that liver injury was caused by mercuric chloride. Treatment with flaxseed oil ameliorated ROS production and reversed enzymes in serum and liver. Also, a noticeable improvement was observed in all the histopathological characteristics in the rats. Conclusions: The findings of this study concluded that flaxseed oil had an outstanding remedial effect on mercuric chloride-mediated hepatic cytotoxicity.
Keywords: Mercury chloride; Flaxseed oil; Hepatotoxicity; Fatty acids; Antioxidant's enzymes